Bisdithiocarbamate and Diamine Interlinked Gold Nanoparticle Networks: Characterization of Chemical Composition and Chemiresistive Properties - Tauchnitz, Tina; Daskal, Yelyena; Dittrich, Rosemarie; Günthel, Michael; Mertens, Florian; Joseph, Yvonne (Frontiers in Sensors, 2022)
Chemiresistive composites of gold (Au) nanoparticles interlinked with different types of organic molecules were prepared automatically by layer-by-layer self-assembly using a microfluidic cell. For the assembly process, dodecylamine-stabilized Au nanoparticles with an average size of 3.7 nm as well as alkyl dithiols, alkyl diamines, and alkyl bisdithiocarbamates with different alkyl chain length (C6 and C8) were used. X-ray photoelectron spectroscopy was applied on prepared nanoparticle composites to study the film composition and the degree of interlinkage. For the measurement of electrical and vapor-sensing properties, silicon dies equipped with gold interdigitated electrodes were used. All films show linear current-voltage characteristics and conductivities in the range of 10–2 and 10–4 Ω−1 cm−1 at room temperature. The sensitivity of the film is investigated by dosing them with vapors of toluene, 1-propanol, 4-methyl-2-pentanone, and water in the concentration range from 100 to 5,000 ppm at 0% relative humidity. All composite films respond with an increase in their electrical resistance to the analytes. The sensors show a high signal-to-noise ratio which indicates a detection limit below 100 ppm for all test vapors. The response dynamics demonstrate a high reversibility and a fast sensing mechanism especially for dithiols and diamines with response and recovery times from 2 to 10 s. The dithiol sensors exhibit a high selectivity to toluene and 4-methyl-2-pentanone whereas the bisdithiocarbamate composites are suitable for the detection of water and 1-propanol. All materials are stable for (at least) several months.